Applied theatre and gender justice : imagination, play, movement - Brenner, Lisa S.; Diaz Cruz, Evelyn (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Applied Theatre and Gender Justice is a collection of essays highlighting the value and efficacy of using applied theatre to address gender in a broad range of settings, identifying challenges, and offering concrete best practices. This book amplifies and shares lessons from practitioners and scholars who use performance to create models of collective solidarity, building upon communities' strengths toward advocating for justice and equity. The book is divided into thematic sections, comprising three essays addressing a range of questions about the challenges, learning opportunities, and benefits of applied theatre practices. Further exploring the themes, issues, and ideas, each section ends with a moderated roundtable discussion between the essays' authors. Part of the series Applied Theatre in Context, Applied Theatre and Gender Justice is an accessible and valuable resource for theatre practitioners and the growing number of theatre companies with education and community engagement programs. Additionally, it provides essential reading for teachers and students in a myriad of fields: education, theatre, civic engagement, criminal justice, sociology, women and gender studies, environmental studies, disability studies, and ethnicity and race studies"--
Keywords: Applied theater; Theater and society; Sex role in the theater; Gender identity in the theater; Social change; SOCIAL SCIENCE / Gender Studies